Analisa Kemampuan Tekuk Komposit Resin Polyester Berpenguat Berbahan Limbah Kain Konveksi - Dinata, I Ketut Aris; Suardana, Ngakan Putu Gede; Kencanawati, Cok Istri Putri Kusuma (Teknik Desain Mekanika; Vol 13 No 2 (2024): April 2024 : Teknik Desain Mekanik, 2024)
Abstract The waste of the fabric has become a common environmental issue in the present time, with the increasing demand for fabric products each year leading to a rise in production. Fabrics made from cotton fibers, blended with chemicals to obtain desired colors and characteristics, pose a threat to the environment by causing pollution. One way to address this is by recycling the fabric waste into composites that can be used for various purposes. This research utilizes fabric volume fractions of 0%, 10%, 20%, and 30% with fabric volume fractions. Bending tests were carried out using ASTM D790-17 and macro photo tests. The bending test data reveals that the addition of fabric reduces stress and elastic modulus up to a certain point. However for strain, the addition of fabric results in lower values compared to the 0% variation, but it increases with the addition of fabric volume. The 30% variation shows a 22% improvement in bending strain compared to the 0% variation. The highest strain is obtained in the 30% variation, and the lowest is in the 10% variation. As for the elastic modulus, the highest value is obtained in the 10% fabric variation, while the lowest is in the 30% variation. Macro photo test results provide insights into the morphology of the composite material, showing that an increased content of convection fabric waste causes the matrix to lose its ability to bind reinforcement, resulting in a decrease in bending strength values. Keywords: Composite, fabric, bending test, polyester resin